2017
DOI: 10.1007/s12094-017-1707-1
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological factors predicting response to neoadjuvant therapy in gastric carcinoma

Abstract: Our study indicates that undifferentiated tumors respond worse to therapy. Furthermore, studies are necessary to define lack of response, to help avoid neoadjuvant therapy in unfavorable cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
6
2
Order By: Relevance
“…pre-intervention parameter, only differentiation was included. A higher differentiation grade was associated with a poorer response to chemotherapy, which is consistent with previous reports (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…pre-intervention parameter, only differentiation was included. A higher differentiation grade was associated with a poorer response to chemotherapy, which is consistent with previous reports (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies [11][12][13][14][15][16] in this treatment setting have proposed small tumor size (but not T stage), differentiated tumor and Laurén intestinal subtype as predictors for histopathologic response to chemotherapy, but there are conflicting results regarding Laurén subtype [17]. We found no other factors than TI and DI to be associated with histopathologic response, though we did not have data on tumor size.…”
Section: Discussioncontrasting
confidence: 58%
“…However, pCR is uncommon, and our data showed that only 13% of patients achieve pCR, similar to previous reports (8.4–17.4%) [ 32 35 ]. A few studies have been devoted to identifying the predictive factors of pCR; possible positive factors include good differentiation of the tumor cells, higher carcinoma embryonic antigen levels and lymphocyte ratios, and lower monocyte counts [ 36 , 37 ]. Patients with these clinical features tend to benefit more from NAC.…”
Section: Discussionmentioning
confidence: 99%